Behavior of Ru–bda Water‐Oxidation Catalysts in Low Oxidation States1. Issue 49 (20th August 2018) - Matheu, Roc; Ghaderian, Abolfazl; Francàs, Laia; Chernev, Petko; Ertem, Mehmed Z.; Benet‐Buchholz, Jordi; Batista, Victor S.; Haumann, Michael; Gimbert‐Suriñach, Carolina; Sala, Xavier; Llobet, Antoni
Abstract: The Ru complex [Ru II (bda‐κ‐N 2 O 2 )(N‐NH2 )2 ] (1 ; bda 2− =2, 2′‐bipyridine‐6, 6′‐dicarboxylate, N‐NH2 =4‐(pyridin‐4‐yl)aniline) was used as a synthetic intermediate to prepare new Ru II and Ru III bda complexes that contain NO +, MeCN, or H2 O ligands. In acidic solution complex1 reacts with an excess of NO + (generated in situ from sodium nitrite) to form a new Ru complex in which the aryl amine ligand N−NH2 is transformed into a diazonium salt [N‐N2 + =4‐(pyridin‐4‐yl)benzenediazonium)] together with the formation of a new Ru(NO) moiety in the equatorial zone, to generate [Ru II (bda‐κ‐N 2 O)(NO)(N‐N2 )2 ] 3+ (2 3+ ). Here the bda 2− ligand binds in a κ‐N 2 O tridentate manner with a dangling carboxylate group. Similarly, complex1 can also react with a coordinating solvent, such as MeCN, at room temperature to give [Ru II (bda‐κ‐N 2 O)(MeCN)(N‐NH2 )2 ] (3 ). In acidic aqueous solutions, a related reaction occurs in which solvent water coordinates to the Ru center to form {[Ru II {bda‐κ‐(NO) 3 }(H2 O)(N‐NH3 )2 ](H2 O) n } 2+ (4 2+ ) and is strongly hydrogen‐bonded with additional water molecules in the second coordination sphere. Furthermore, under acidic conditions the aniline ligands are also protonated to form the corresponding anilinium cationic ligands N‐NH3 + . Additionally, the one‐electron oxidized complex {[Ru III {bda‐κ‐(NO) 3.5 }(H2 O)(N‐NH3 )2 ](H2 O) n } 3+ (5 3+ ) was characterized, in which the fractional value in the κ notation indicates the presence of an additional contact to the pseudo‐octahedral geometry of the Ru center. The coordination modes of the complexes were studied in the solid state and in solution through single‐crystal XRD, X‐ray absorption spectroscopy, variable‐temperature NMR spectroscopy, and DFT calculations. While κ‐N 2 O is the main coordination mode for2 3+ and3, an equilibrium that involves isomers with κ‐N 2 O and κ‐NO 2 coordination modes and neighboring hydrogen‐bonded water molecules is observed for4 2+ and5 3+ . Abstract : Lost and found coordination : Ru–bda (bda=2, 2′‐bipyridine‐6, 6′‐dicarboxylate) catalysts are powerful water‐oxidation catalysts thanks to the sevenfold coordination provided by the ligand framework. While heptacoordination provides stability when the Ru complex reaches high oxidation states, the Ru center can only have six of these positions coordinated in the first catalytic steps. Herein, this coordination rearrangement (see scheme) was studied by characterizing new Ru–bda complexes by techniques including variable‐temperature NMR spectroscopy, X‐ray absorption spectroscopy, and single‐crystal XRD.